A COMPARATIVE STUDY ON EFFICACY AND SAFETY OF STREPTOKINASE AND RETEPLASE IN PATIENTS WITH MYOCARDIAL INFARCTION IN A TERTIARY CARE TEACHING HOSPITAL - MUTHULAKSHMI R,; JAMUNARANI R,; JANANI L,; SOWMINI K, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study compares the efficacy, safety, and cost-effectiveness of streptokinase and reteplase in treating patients with acute myocardial infarction (AMI) at SRM Hospital. A total of 86 patients were divided into two groups, each receiving either streptokinase or reteplase, with outcomes tracked over a 3-month period. Methods: Over the course of 3 months, the results of 86 patients who were split into two groups and given either reteplase or streptokinase were monitored. Results: The duration of hospital stays (6.05 days vs. 9.79 days) and the time it took to relieve symptoms (4.58 h vs. 8.74 h for streptokinase) were both significantly shortened by reteplase, according to the results. However, streptokinase was found to be more cost-effective. Both treatments showed similar increases in creatine phosphokinase (CPK) and CPK-MB biomarkers post-thrombolysis, but reteplase demonstrated superior efficacy. While reteplase was associated with a higher incidence of bleeding, streptokinase had more cases of hypotension and hypersensitivity. No significant mortality or morbidity was observed during the study period. Conclusion: This study highlights the clinical advantages of reteplase over streptokinase, despite its higher cost.